Integration of migrants into the country’s social environment: the case of Lithuania - Meidutė-Kavaliauskienė, Ieva; Činčikaitė, Renata (Business: Theory and Practice, 2023)
Migration is one of today’s most sensitive and relevant topics. In 2022 alone, 32.5 million people worldwide will have left their country due to war, political instability, economic hardship, climate change, and other reasons. In recent years, the constantly growing flow of migrants to developed countries poses increasing challenges to the institutions and organizations of those countries, which are looking for new ways of integrating migrants into the social environment. It is difficult for state institutions that do not have the right tools to assess the integrity of the state, and it is difficult to control the ongoing migration processes and quickly make decisions regarding the increased flows of migrants, which could be solved promptly with minimal use of resources. One of the most important solutions for overcoming the challenges of migration is using a dynamic complex instrument that would allow us here and now to identify the causes of changes and efficiently mobilize the necessary resources to solve the challenges of migration that are usually not planned. The article aims to form a complex evaluation instrument to integrate migrants into the social environment. To achieve the goal, a systematic, comparative analysis of concepts and methods published in the scientific literature, statistical processing, and multi-criteria evaluation methods (COPRAS), and the method of determining weight coefficients (CRITIC) is applied.